1986
DOI: 10.1128/jvi.58.1.107-115.1986
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibody cure and prophylaxis of lethal Sindbis virus encephalitis in mice

Abstract: hemagglutination, and antiserum to E2 neutralizes infectivity (11), but monoclonal antibodies (MAbs) to either glycoprotein can inhibit hemagglutination, neutralize infectivity, or both (9, 35, 36, 38). E2 may be an important determinant of virulence (30, 38). Recently Schmaljohn et al. (35) showed that neutralizing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 35 publications
2
27
0
Order By: Relevance
“…The B cells producing these antibodies are first detected in the spleens of infected animals before appearing in the brain (Tyor and Griffin, 1993), although their need to physically traverse the BBB in order for antibodies to reach foci of infection is debatable. Indeed, prior studies have shown that the intravenous transfer of immune serum or monoclonal anti-viral antibodies is sufficient to promote viral clearance and recovery in SV-infected mice, provided that enough material is given (Stanley et al, 1986;Levine et al, 1991). In this disease setting, the influx of B cells into the CNS may be more important to establish a local population of anti-viral effectors that are retained at that site well after viral clearance has been achieved in order to prevent late viral recrudescence (Tyor et al, 1992;Griffin et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The B cells producing these antibodies are first detected in the spleens of infected animals before appearing in the brain (Tyor and Griffin, 1993), although their need to physically traverse the BBB in order for antibodies to reach foci of infection is debatable. Indeed, prior studies have shown that the intravenous transfer of immune serum or monoclonal anti-viral antibodies is sufficient to promote viral clearance and recovery in SV-infected mice, provided that enough material is given (Stanley et al, 1986;Levine et al, 1991). In this disease setting, the influx of B cells into the CNS may be more important to establish a local population of anti-viral effectors that are retained at that site well after viral clearance has been achieved in order to prevent late viral recrudescence (Tyor et al, 1992;Griffin et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The method for measuring complement-mediated lysis of infected cells was a modification of a protocol to quantitate complement-mediated lysis of Sindbis virus-infected cells (61). Briefly, MC57GL cells were infected at a multiplicity of infection (MOI) of 5 or mock infected.…”
Section: Methodsmentioning
confidence: 99%
“…In more recent experiments using an otherwise lethal strain of Sindbis virus, animals preimmunized against nonstructural viral proteins were highly protected against permanent paralysis and death (Gorrell et al, 1997). This protection was not associated with either reduced virus replication in the brain or altered virus tropism (neurons of the brain and spinal cord remained the principal target of infection), nor was it due to an augmented humoral response against structural viral proteins that could also protect lethally infected animals (Stanley et al, 1986;Gorrell et al, 1997). Instead, this nonstructural proteinmediated protection proved to be a function of immune T cells and occurred by promoting the survival and functional recovery of virus-infected neurons (Gorrell et al, 1997).…”
Section: T Cells Can Protect Hosts From Lethal Cns Viral Infectionmentioning
confidence: 98%